Inducing Isotropic Growth in Multidimensional Cesium Lead Halide Perovskite Nanocrystals. Issue 6 (21st June 2018) - Bhaumik, Saikat; Veldhuis, Sjoerd A; Muduli, Subas Kumar; Li, Mingjie; Begum, Raihana; Sum, Tze Chien; Mhaisalkar, Subodh; Mathews, Nripan
Abstract: A new two‐step synthetic protocol to yield monodisperse spherical zero‐dimensional (0D) Cs4 PbX6 nanocrystals (NCs) and three‐dimensional (3D) CsPbX3 NCs is described. The first step of the reaction involves the colloidal synthesis of spherical PbX2 seed NCs, which are subsequently converted to Cs4 PbX6 and CsPbX3 NCs through hot injection of a Cs precursor at the desired reaction temperatures. By employing less reactive Pb and halide precursors, the reaction time was extended from several seconds to about five minutes, thereby allowing greater control during the crystallization and growth stages. The adjustment of halide ratios allows color tuning over a wide spectral range (411–669 nm) for CsPbX3 NCs, with high photoluminescence quantum yields (6–65 %) and narrow emission line widths (ca. 13–30 nm). We envisage our spherical NCs to become a starting point for shell growth (e.g., ZnS, CdS, PbS) by overcoming the difficulty of shell growth around thermodynamically unfavorable (i.e., high surface free energy) cuboid‐shaped NCs. Abstract : Another dimension : A new two‐step synthetic protocol to yield monodisperse spherical zero‐dimensional Cs4 PbX6 nanocrystals (NCs) and 3D CsPbX3 NCs through hot injection of a Cs precursor in pre‐synthesized spherical lead halide (PbX2 ) seed NCs at different reaction temperatures is described (see scheme).